2016
DOI: 10.2337/db16-0099
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Genetic Metabolic Cause for Mauriac Syndrome in Type 1 Diabetes

Abstract: A mechanistic cause for Mauriac syndrome, a syndrome of growth failure and delayed puberty associated with massive liver enlargement from glycogen deposition in children with poorly controlled type 1 diabetes, is unknown. We discovered a mutation in the catalytic subunit of liver glycogen phosphorylase kinase in a patient with Mauriac syndrome whose liver extended into his pelvis. Glycogen phosphorylase kinase activates glycogen phosphorylase, the enzyme that catalyzes the first step in glycogen breakdown. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 31 publications
(26 reference statements)
0
29
0
1
Order By: Relevance
“…While Mauriac syndrome is invariably observed in the setting of poor glycemic control, only a small fraction of T1DM patients with elevated HgbA1c develop the condition, suggesting that additional risk factors must exist. A potential genetic cause was recently described by MacDonald and colleagues who studied a 13 year old boy with Mauriac syndrome severe enough to cause liver impingement on the diaphragm and respiratory distress 32 . Sequential sequencing of candidate genes in the glycogen metabolism pathway revealed a heterozygous mutation of a highly conserved amino acid in the phosphorylase kinase γ subunit 2 ( PHKG2 ) gene.…”
Section: Growth Following the Onset Of T1dmmentioning
confidence: 95%
“…While Mauriac syndrome is invariably observed in the setting of poor glycemic control, only a small fraction of T1DM patients with elevated HgbA1c develop the condition, suggesting that additional risk factors must exist. A potential genetic cause was recently described by MacDonald and colleagues who studied a 13 year old boy with Mauriac syndrome severe enough to cause liver impingement on the diaphragm and respiratory distress 32 . Sequential sequencing of candidate genes in the glycogen metabolism pathway revealed a heterozygous mutation of a highly conserved amino acid in the phosphorylase kinase γ subunit 2 ( PHKG2 ) gene.…”
Section: Growth Following the Onset Of T1dmmentioning
confidence: 95%
“…Recently, a mutation in an enzyme of glycogen metabolism (catalytic subunit of glycogen phosphorylase kinase) was reported in a patient with Mauriac syndrome that increases glycogen content by limiting glycogen breakdown and hence increasing its deposition in the human liver. The postulated mechanism is that this mutant enzyme of glycogen metabolism combines with hyperglycemia to directly inhibit glycogen phosphorylase, resulting in many of the phenotypic features observed in this syndrome …”
Section: Growth Weight Gain and Pubertal Developmentmentioning
confidence: 99%
“…Such studies have recently been reported by MacDonald et al [28]. The authors noted that the mutation in PHKG2 (phosphorylase kinase catalytic subunit gamma 2), combined with hyperglycaemia, together with glycogenolysis, caused severe hepatomegaly.…”
Section: Discussionmentioning
confidence: 70%